Multi-omics analysis to uncover the molecular basis of tumor budding in head and neck squamous cell carcinoma - Ourailidis, Iordanis; Stögbauer, Fabian; Zhou, Yuxiang; Beck, Susanne; Romanovsky, Eva; Eckert, Stephan; Wollenberg, Barbara; Wirth, Markus; Steiger, Katja; Kuster, Bernhard; Gires, Olivier; Stenzinger, Albrecht; et al. (npj precision oncology, 2025)
Tumor budding (TB) is a prognostic biomarker in HPV-negative and HPV-positive head and neck squamous cell carcinoma (HNSCC). Analyzing TCGA and CPTAC mutation, RNA, and RPPA data and performing proteomics and IHC in two independent in-house cohorts, we uncovered molecular correlates of TB in an unprecedentedly comprehensive manner. NSD1 mutations were associated with lower TB in HPV-negative HNSCC. Comparing budding and nonbudding tumors, 66 miRNAs, including the miRNA-200 family, were differentially expressed in HPV-negative HNSCC. 3,052 (HPV-negative HNSCC) and 360 (HPV-positive HNSCC) RNAs were differentially expressed. EMT, myogenesis, and other cancer hallmarks were enriched in the overexpressed RNAs. In HPV-negative HNSCC, 88 proteins were differentially expressed, significantly overlapping with the differentially expressed RNAs. CAV1 and MMP14 protein expression investigated by IHC increased gradually from nonbudding tumors to the bulk of budding tumors and tumor buds. The molecular insights gained support new approaches to therapy development and guidance for HNSCC.
Gesehen am 19.08.2025